Organic onion biofortification using microalgae and humic acid (Research, Society and Development, 2021)
Biofortification can be understood as a strategy to raise nutrients levels in vegetables edible structures, which can positively interfere in human diet. Biofertilizers are an interesting option in alternative production systems, as they can increase food nutritional quality and contribute to plant development, while aiding environment sustainability as natural products. The use of microalgae and humic acid as biofertilizers points to improvements in nutrients and biomolecules content in plants, however, their combined application is still unexplored. In that scenario, it was carried a study with onions about the influence of applications via root immersion in microalgae Scenedesmus subspicatus (Sc) and humic acid (HA) solutions, analyzing possible alterations of macro and micronutrients, total sugars, reducing sugar, free total amino acids, , total soluble solids,  soluble proteins and antioxidant capacity in the bulbs. Treatments consisted of one minute seedlings roots immersion from two onion cultivars in solutions containing microalgae and humic acid, and then transplanted to organic system field. There were used three concentrations: control, 0.3 g L-1 Sc + 0.3 g L-1 HA (3SH) and 0.6 g L-1 Sc + 0.6 g L-1 HA (6SH). Results show that the treatments with microalgae with humic acid association were able to increase the content of N, carbohydrates and soluble proteins, also elevating antioxidant activity in onion bulbs.